Four -Fold Function Implementation and Organizational Climate of The State University In Capiz - ROSELYN PRECIOSA CABANTUD (Faculty of Business, President University, 2023)
This study aimed to determine the extent of the four-fold function implementation and the degree of organizational climate of the State University in Capiz for the academic year 2022-2023. The study used a mixed-method research design. A quantitative and qualitative approach was employed in gathering the data from randomly selected respondents. A total of two hundred twenty-two (222) teaching staff and school heads were for quantitative data and fifteen (15) parents for the qualitative data. Statistical tools used to analyze quantitative data were frequency count, percentage, mean, t – test, Analysis of Variance and Spearman rank correlation analysis. Qualitative data were being analyzed and interpreted using the seven stages of conducting in-depth interviews: thematizing, designing, interviewing, transcribing, analyzing, verifying, and reporting. The findings of the study revealed that the four-fold functions implementation and organization climate of the State University in Capiz were to a high extent. The extent of the four-fold function implementation of the State University in Capiz was the same regardless of highest educational attainment, type of employment, number of years in service, and monthly income of teaching staff and school heads. The degree of organizational climate at the State University varies based on the employment status of the respondents, and there is a significant relationship between the extent of four-fold function implementation and organizational climate at the University in Capiz. It is recommended to conduct a study on the impact of digital transformation on organizational culture. Furthermore, other variables, research designs, and approaches should be considered to widen the scope of the research.